Determination of the Causes of Job Mobility in Employment - Jibril, Hadira Thumaninah (Hasanuddin Economics and Business Review, 2023)
The purpose of this study is to examine and identify the factors that contribute to job mobility (changing jobs) among employees in Makassar City's informal sector. 100 respondents provided the primary data that was used. There were 28 variables under investigation, and factor analysis was used to process the data. Further analysis is possible for a total of 21 variables. The significance value in the validity test was over 0.05, hence the remaining 7 variables were eliminated. According to the study's findings, there are seven elements that influence people's decisions to change jobs. These variables include economic factors, labor quality factors, information technology proficiency factors, length of working hours factors, family factors, employment status factors, and distance factors.